HUBUNGAN ANTARA HARDINESS DENGAN SELF-EFFICACY PADA LANSIA MASIH BEKERJA DI BANGUNTAPAN BANTUL - Feranita Indriati; Titik Muti’ah (JURNAL SPIRITS, 2015)
ABSTRACT This research aims to know the relationship between hardiness and self-efficacy of lansia (elderly) who still works in Banguntapan Bantul. The Hypotheses in this research is the relationship between hardiness and self-efficacy of lansia (elderly) who still works in Banguntapan Bantul.Subject of this research are working lansia (elderly) to men and women working lansia (elderly) with ages around 65 until 70 years old they are men and women that has total of 70. The the data was collected by using instrument used hardness and self-efficacay scale. The data was analysised using pearson product moment correlation with program SPSS Version 16 for Windows.The result of the analysis, showed that the correlation was between variable hardiness and self-efficacy 0,713 with P=0,00. This result and true the hypotheses was accepted meaning there is a relationship between hardiness and self-efficacy. It means that whenever the self-efficacay in lansia (elderly) are highest so the the hardiness are highest too. And the other way, if the self efficacy in lansia (elderly) are lowest so the hardiness are lowest too. Keywords : Hardiness, Self Efficacy, and Lansia (Elderly)